Prevalence and risk factors for leishmaniasis and Chagas disease in the canine population of the tourist city of Ibiuna, Sao Paulo, Brazil - Mascolli, Roberta; Martins Soto, Francisco Rafael; Pinheiro, Sonia Regina; Ito, Fumio Honma; Gil, Aline; Azevedo, Sergio Santos de; Felix de Lima, Valeria Maral [UNESP]; Langoni, Helio [UNESP]; Fonseca Fernandes, Annielle Regina da; Vasconcellos, Silvio Arruda (Univ Estadual Londrina, 2016)
The aims of the study were to determine the seroprevalence of leishmaniasis and Chagas disease, and to determine the risk factors associated with seropositivity in dogs in the tourist city of Ibiuna, Sao Paulo, Brazil. A total of 570 blood samples of dogs were collected from four regions in the 48 districts of the municipality, from September 2007 to March 2008, and submitted for serological examination. Laboratory diagnosis of leishmaniasis and Chagas disease was performed using indirect enzyme-linked immunosorbent assay and indirect immunofluorescence, respectively. Of the 570 animals examined, 13 (2.3%; 95% confidence interval [CI] = 1.2%-3.8%) were seropositive for leishmaniasis, and 35 (6.1%; 95% CI = 4.3%-8.3%) were seropositive for Chagas disease. A risk factor associated with seropositivity for Chagas disease in dogs was residence in a region with a predominance of small farms generally used for subsistence planting and leisure and surrounded by forest areas (odds ratio = 4.20). By contrast, there were no risk factors identified for leishmaniasis, leading us to conclude that leishmaniasis and Chagas disease are present in dogs in the tourist city of Ibiuna, Sao Paulo; however, additional studies are needed in order to fully define the risk factors associated with disease in this municipality.
Keywords: Dogs; Epidemiology; Leishmania spp; Southeastern Brazil; Trypanosoma